PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN DESA MANDIRI BENIH PADI ORGANIK UNTUK PENINGKATAN PENDAPATAN DI DESA TOMPOBULU, KECAMATAN TOMPOBULU, KABUPATEN MAROS: Community Empowerment through Development of Organic Rice Seed Self-governing Village to Increase Income of Farmers at Tompobulu Village, Tompobulu District, Maros Regency - A. Syaiful, Syatrianty; Kasim, Nurlina; Busthanul, Nurbaya; Baba, Basri; Oktaviany, Amelia; E. Mahmud, Fadjrin; Iswari, Inez (Jurnal Dinamika Pengabdian, 2021)
ABSTRAK Peluang agribisnis pertanian organik khususnya padi organik terbuka luas bagi petani khususnya yang tergabung dalam kelompok tani karena tingginya permintaan konsumen pada hasil pertanian organik yang sangat baik bagi kesehatan dan juga bernilai ekonomi tinggi. Masalah yang dihadapi adalah minimnya pengetahuan petani tentang produksi tanaman padi organik dan penggunaan benih organik bermutu untuk menunjang produksi tanaman. Kegiatan pengabdian dilaksanakan pada Mitra Kelompok Tani Botolempangan, Dusun Baddo Ujung, Desa Tompobulu Kecamatan Tompobulu, Kabupaten Maros. Kegiatan ini berupa alih iptek ke petani untuk meningkatkan pendapatan petani melalui usaha perbenihan padi organik, pengolahan limbah pertanian (biomassa tanaman dan limbah ternak) menjadi pupuk organik dan pembuatan pestisida organik untuk digunakan dalam budidaya padi. Metode yang digunakan dalam pelaksanaan kegiatan adalah: penyuluhan/pendampingan teori dan pelatihan/pendampingan  praktek. Paket teknologi yang diintroduksi berupa teknik pembuatan pupuk organik dari limbah pertanian (padat dan cair) alami yang sumber bahan bakunya berbasis lokal, teknik produksi benih padi organik dan teknik budidaya padi berbasis produk alami mulai dari persiapan lahannya sampai pascapanen. Hasil PKM menunjukkan bahwa petani sangat antusias dalam mempelajari sistem pertanian padi organik. Hal tersebut  terlihat dari kehadiran Dinas Pertanian setempat dan tingkat kehadiran petani yang rata-rata tinggi yaitu sekitar 40 orang dari 20 orang yang di undang pada semua tahapan kegiatan. Lahan percontohan terpelihara dengan sangat baik sehingga pertumbuhan dan perkembangan tanaman juga sangat baik. Kata kunci: Pertanian organik, benih organik, padi organic, desa mandiri benih, pemberdayaan petani.   ABSTRACT Opportunities for organic farming agribusiness, especially organic rice, are wide open for farmers, especially those who are members of farmer groups because of the high consumer demand for organic agricultural products which are very good for health and also have high economic value. The problem faced is the lack of knowledge of farmers about organic rice crop production and the use of quality organic seeds to support crop production. The community service activities were carried out at the Mitra Perkasa Tani Botolempangan, Baddo Ujung Hamlet, Tompobulu Village, Tompobulu Subdistrict, Maros Regency. This activity is in the form of transferring science and technology to farmers to increase farmers' income through organic rice seeding businesses, processing agricultural waste (plant biomass and livestock waste) into organic fertilizers and making organic pesticides for use in rice cultivation. The methods used in the implementation of the activity are: counseling / theoretical assistance and training / practical assistance. The technology package introduced was in the form of techniques for making organic fertilizers from natural (solid and liquid) agricultural waste with local-based raw material sources, organic rice seed production techniques and rice cultivation techniques based on natural products ranging from land preparation to post-harvest. PKM results show that farmers are very enthusiastic in studying the organic rice farming system. This can be seen from the presence of the local Agriculture Office and the high level of farmer attendance, which is about 40 out of 20 people invited to all stages of the activity. The demonstration plot is very well preserved so that the growth and development of plants is also very good. Keywords: Organic farming, organic seeds, organic rice, self-sufficient seeds villages, empowerment of farmers.